ANALISIS MATERI BAB II “DI BAWAH ATAP” BUKU AJAR BAHASA INDONESIA UNTUK SISWA KELAS IV BERDASARKAN KELAYAKAN BUKU BSNP - Intan Assyifaur Rakhmah; Panca Dewi Purwati; Deslyani Rambu Kapu; Devy Atika Kumala Sari; Muhyddin; Annisa Eka Handayani (STKIP Subang, 2025)
Textbooks play an important role as primary learning resources for elementaryschool students. It is essential to ensure that these books comply with thestandards set by the National Education Standards Agency (BSNP). This studyaims to analyze the alignment of textbooks with BSNP standards in terms ofcontent quality, language quality, presentation quality, and graphic quality. Aqualitative descriptive approach was used, employing a textbook analysis method.The results indicate that most textbooks meet the content quality standards,particularly in terms of alignment with and development of core competencies.However, weaknesses were identified in the linguistic and graphic aspects, suchas the use of terms that are not appropriate for students' developmental level andfont sizes and layout structures that do not comply with ISO standards. Thesefindings are consistent with previous research emphasizing the importance ofaligning materials with BSNP standards. Therefore, it is recommended that thecontent in Chapter II, “Under the Roof,” be revised to enhance the depth ofmaterial and adjust the language to better align with BSNP standards. Ensuringthat the textbook functions as an effective learning resource is crucial to meetingthe needs of fourth-grade students.